Programa educativo gamificando para mejorar la motivación académica en estudiantes de educación física octavo ciclo Facultad de Ciencias de la Educación y Humanidades Universidad Nacional de la Amazonía Peruana Iquitos 2023 - Rengifo Ruiz, Molly Danae (2024)
The primary objective of the research was to assess how the introduction of the 'Gamifying' educational program influenced the enhancement of scholarly enthusiasm among students enrolled in the Eighth Cycle Physical Education course at the Faculty of Education and Humanities, National University of the Peruvian Amazon, Iquitos, during the year 2023. An evaluative methodological approach characterized by a univariate, field-based, and cross-sectional design was adopted. The target population consisted of 40 students, who also formed the study sample. Data collection utilized a questionnaire previously validated by subject matter experts using survey technique. Results: Following the implementation of the educational program Gamifying on student academic motivation, significant changes in motivation levels were observed. The percentage of students with high motivation levels increased significantly from 25.0% (10 students) to 80.0% (32 students), while the medium level experienced a decrease from 67.5% (27 students) to 20.0% (8 students). There was a substantial improvement in the low level, decreasing from 7.5% (3 students) to 0.0% post-intervention. Conclusions: The results indicate that implementing the educational program Gamifying had a positive impact on academic motivation for Physical Education students at the UNAP. The notable increase in high motivation levels, coupled with the decrease in medium and low levels, confirms the effectiveness of this program in enhancing student motivation. These findings underscore the importance of further research into innovative educational strategies like Gamifying to enhance academic motivation and foster greater engagement in the learning process for Physical Education students.